THE MULTILINGUAL BRAIN: UNVEILING COGNITIVE AND NEURAL DYNAMICS IN LANGUAGE LEARNING - Samia Ilhem NOUADR (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2024)
In today's world, where multilingualism has become the norm and monolinguals are in the minority, academic research has been slow to adapt to this reality. This phenomenon, which highlights the human brain's ability to master multiple languages whether it be the native language (L1), a second language (L2), or even a third language (L3) calls for a reevaluation of traditional paradigms. This study aims to challenge conventional approaches in cognitive linguistics, particularly those related to language acquisition, language choice, and the underlying cerebral processes. The research questions addressed include: how individuals navigate between multiple languages in various cognitive and social contexts, and what are the implications for our understanding of human cognitive abilities? The methodology employed combines experimental analyses using brain imaging, psycholinguistic testing, and sociolinguistic surveys of multilingual speakers. The findings reveal that bilingualism and multilingualism not only enhance cognitive flexibility but also improve problem-solving abilities and adaptability in multicultural environments. In conclusion, this study demonstrates that multilingualism is not merely the acquisition of multiple linguistic systems, but a complex phenomenon that impacts cognition, social interactions, and brain structures. By redefining our understanding of cognitive and linguistic processes, this research proposes new paradigms for studying language in a globalized context.